Short-term side effects of COVID-19 vaccines: A cross-sectional study in Jordan - Razan I. Nassar; Dalal Alnatour; Samar Thiab; Ayman Nassar; Feras El-Hajji; Iman A. Basheti (Taylor & Francis Group, 2022)
The rapid manufacturing of vaccines has increased hesitancy toward receiving the COVID-19 vaccines. Clarifying what to expect after vaccination and revealing the possible side effects will lower hesitancy toward receiving the COVID-19 vaccine and increase public awareness. This descriptive cross-sectional survey-based study was conducted in Jordan (August 2021) to collect data on the short-term side effects following the COVID-19 vaccines. An extensive literature review was conducted by the research team to assist in developing the first draft of the survey. The survey was tested for face and content validity and piloted test to improve readability and clarity. The survey was organized into two sections (demographics and perceived COVID-19 vaccines' side effects). Data were analyzed using the Statistical Package for Social Science (SPSS). A total of 1,044 participants were enrolled in the study. The most received vaccine among the participants was Pfizer-BioNTech (51.1%). The most frequently reported side effects were sore arm at the injection site (84.65%), fatigue (84.48%), discomfort (65.43%), muscles/joint pain (61.38%), drowsiness (58.73%), and headache (58.38%). More side effects were significantly associated with being older (p = 0.046), having an allergy (p = 0.024) or rheumatoid arthritis (p = 0.023), and participants who take NSAIDs regularly (p = 0.029). Short-term side effects of COVID-19 vaccines seem to be mostly local or transient in nature. Older age and certain comorbidities may increase susceptibility to side effects.